(untitled) (Scottish Archaeological Internet Reports, 2004)
A detailed account of the excavation methodology is followed by an archaeological description. Trench 1 had been very disturbed by bulldozing for the new trackway. Four squares within the trench were excavated. Two cultural contexts contained flaked lithics and charcoal as well as several stones. Some of the stones may have outlined part of a hearth. Two scoops were cut into the raised beach. Four text pits contained lithics and three soil pits were dug for specialist analyses. Lithics were also found at two further locations.